Development of fishery marketplace app for fishermen to support local products during the covid-19 pandemic - Kurniawan, Dwi Ely; Dzikri , Afdhol; Herman, Nanna Suryana (Association for Scientific Computing Electrical and Engineering, 2021)
Since the Covid-19 pandemic, the growth of E-commerce in Indonesia has increased sharply. The COVID-19 pandemic has caused a shift in human habits or activities from offline to online. However, the lack of facilities and infrastructure, especially the fish auction place, is an obstacle fishers face when they want to market and distribute their catch. This study aims to provide an alternative solution to the limitations of fish auction places. This research develops a prototype of a fishery marketplace application to make it easier for fishers to market their catch. The research method in software development uses a prototyping model and usability testing using the SUS scale. Based on fishermen's gadgets owned, including network infrastructure availability in hinterland areas. This study used technology that utilizes SMS Gateway. SMS messages in the form of information on fish products. Based on the analysis and calculation of the SUS score, the result is 79.25, meaning that the fisherman's application is functionally perfect and can be accepted by users. The fisheries marketplace application displays a catalog of fish products that can access the public to view product information, prices, and transact. Buyers and sellers meet in the fisheries marketplace application to make offers via call communication or take advantage of the provided WhatsApp API.